A Relativistic Eschatology: Time, Eternity, and Eschatology in Light of the Physics of Relativity - Jackelén, Antje (Zygon, 2006)
Abstract. Unique epistemological challenges arise whenever one embarks on the critical and self-critical reflection of the nature of time and the end of time. I attempt to construct my preference for an eschatological distinction between time and eternity from within a middle way, avoiding both the hubris that claims complete comprehension and the resignation that concedes readily to know nothing. Surveying the history of reflection on this multifaceted question of time, with its ephemeral and everlasting dimensions, I argue that the eschatological interplay between the “already” and the “not yet” has much to offer: promise for the religion-science dialogue as well as hope for humanity, especially for those on society's bleakest edges. But understandings of time, to be authentically theological, must be also informed by cosmology and the physics of relativity. My proposal seeks to respect the theological and scientific interpretations of the nature of time, serving the ongoing, creative interaction of these disciplines. Between physics and theology I identify four formal differences in analyzing eschatology, all grounded in the one fundamental difference between extrapolation and promise. Discussion of what I term deficits in both the scientific and theological approaches leads to further examination of the complex relationship between time and eternity. I distinguish three models of such relationships, which I label the ontological, the quantitative, and the eschatological distinction between time and eternity. Because of the way it embraces a multiplicity of times, especially relating to the culmination and the consummation of creation, I opt for the eschatological model. The eschatological disruption of linear chronology relates well to relativ-istic physics: This model is open, dynamic, and relational, and it may add a new aspect to the debate over the block universe.